Evaluation of methods to quantify populations of the coffee berry borer Hypothenemus hampei (Ferrari) (Coleoptera: Curculionidae: Scolytinae), in farms of coffee growers experimenters - TRUJILLO-E., HÉCTOR IVÁN; ARISTIZÁBAL-A., LUIS FERNANDO; BUSTILLO-P., ALEX ENRIQUE; JIMÉNEZ-Q., MAURICIO (Revista Colombiana de Entomología, 2006)
Through participatory research two methods for sampling the abundance of coffee berry borer (CBB) populations were compared in the field with the objective of contributing to the integrated management of this insect. This experiment was carried out on 11 farms: four in Quimbaya, two in Belalcazar, one in Viterbo, three in Balboa and one in Risaralda. One commercial coffee plot was selected from each farm and CBB infestation was evaluated using two methods: 30-Branch Method (the number of green fruits per branch and the number of fruits infested by CBB are quantified, followed by determination of percent infestation). Measure Method (initially, the distance that contains 50 green fruits is assessed through direct measurement in100 branches; this distance is then used to make the monthly samplings counting the fruits infested in only 30 branches; finally the percent infestation is determined). The 30-branch sampling plan obtained similar results to the measure method, but the latter requires less time. The different levels of CBB infestation were similar between the two sampling methods. The coffee growers show interest in continuing to evaluate this new sampling method (measure method). They indicated that with this new sampling method they can save more time.